The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5114/reum.2020.100112
|View full text |Cite
|
Sign up to set email alerts
|

Calcium physiology, metabolism and supplementation: a glance at patients with ankylosing spondylitis

Abstract: The aim of this review is to describe the metabolism of calcium in ankylosing spondylitis compared to physiologic conditions, and to present the current evidence on the benefits and disadvantages of calcium supplementation in these patients. A narrative review of the literature was conducted using the PubMed database and a total of 65 articles were selected. Calcium is involved in many physiopatholo­gical processes, including inflammation, bone loss and bone formation, all of which occur in ankylosing spondyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
(93 reference statements)
0
7
0
1
Order By: Relevance
“…Despite the tendency toward osteophytes, the increased risk of osteoporosis in AS may be based on chronic inflammation, lack of exercise, and malabsorption, and therefore calcium and vitamin D supplementation are often required. 5 the onset of AS. It is not the cause of AS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the tendency toward osteophytes, the increased risk of osteoporosis in AS may be based on chronic inflammation, lack of exercise, and malabsorption, and therefore calcium and vitamin D supplementation are often required. 5 the onset of AS. It is not the cause of AS.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has been found that minerals may be involved in the pathology of AS. [4][5][6][7][8] A previous study has found that metal triggers conformational reorientation of a self-peptide bound to a disease-associated human leukocyte antigen-B27 (HLA-B27) subtype and suggests that metals may have a role in triggering rheumatic diseases such as AS. 4 Inflammation and the progressive fusion calcification of axial joints are typical features of AS.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations